Post-traumatic stress symptoms in an Italian cohort of subjects complaining occupational stress. (14th October 2021) - Buselli, Rodolfo; Carmassi, Claudia; Corsi, Martina; Baldanzi, Sigrid; Battistini, Gianmarco; Chiumiento, Martina; Massimetti, Gabriele; Dell'Osso, Liliana; Cristaudo, Alfonso
Abstract: Objective: Work-related stress presents a significant impact on work performance and physical health. It has been associated with the onset of a multitude of symptoms. The main aim of this investigation is to better understand the impact of post-traumatic stress symptomatology, using a specific self-assessment questionnaire, in subjects experiencing occupational stress with the rationale to address the variegated symptoms expressed by this particular population in a post-traumatic dimensional perspective. Methods: Authors collected socio-demographic, occupational, and clinical data. They utilized Trauma and Loss Spectrum Self Report (TALS-SR), a questionnaire investigating post-traumatic stress symptoms. The population size was 345 subjects who presented at the Occupational Health Department of a university hospital over a 3 years period (2016–2018). Results: Data analysis revealed 33.9% of subjects who met post-traumatic stress disorder (PTSD) criteria. Gender distribution of this set was (36.4% female, 31% male). A family history or personal history of mental disorders were related to higher scores in almost all TALS-SR domains and were related, respectively, to higher scores of criterion B "intrusion symptoms" ( P = .014), criterion D "negative alterations in cognitions and mood" ( P = .023), and criterion E "arousal" ( P = .033) of PTSD. Differences in TALS-SR scores also emerged based on age and gender. Conclusions: PTSD symptoms manifest at a significant level in those who experience work-related stress. Personal background of individuals, both in terms of family and personal history for mental disorders, seems to increase their vulnerability to develop post-traumatic stress symptoms. This study suggests the importance of evaluating occupational stress from a post-traumatic stress perspective also at an early stage.